An analysis of Satire Delivered by Politic Observer Rocky Gerung in Indonesia Lawyer Club (ILC) - Rafi Andry; Hermawati Syarif (English Language and Literature, 2021)
In delivering critics, the use of satire is indispensable so that the critics can be accepted or heard, because satire is very much used as a tool to convey the critics. This study aims to analyze the types and techniques of satire introduced by Abeshaus (2018) and Luke Endley (2017). The method used in this research is descriptive method. There are two problems in this study, (1) what types and (2) technique of the satire used by Rocky Gerung in his speech. The results show that in 24 techniques  of satire there are 14 techniques of satire with Inflation (38.9%), Hyperbole (14.9%) and Innuendo (14.9 %) being the highest found and from 3 types of satire were found that Juvenalian (57.3%) as the dominant type. The result of this research is that Rocky Gerung tends to use critics by using Inflation with exaggerating the mistakes and circumstances. Regarding the type, the most commonly type found in this study is the Juvenalian type. Because Rocky Gerung tends to use the type of sarcasm that is harsh and reproachful